Geochronology and geochemistry of Early Cretaceous high-silica granites in the Nan'ao Island, South China: Petrogenesis and implications for lithospheric extension. (15th April 2023) - Zhou, Dawn; Sun, Peng; Jiang, Shijun; Liu, Xiao; Wang, Qiang
Graphical abstract: Highlights: The Nan'ao Island granites were formed at Early Cretaceous (141–121 Ma) The Nan'ao Island granites were mainly derived from juvenile crustal rocks. Melting of juvenile crustal rocks was linked to rollback of the Paleo-Pacific plate. Abstract: Widespread Late Mesozoic granites in South China are known to be younger southeastward, which is important for understanding the tectonic-magmatic evolution in South China. However, previous studies assumed Jurassic or Late Cretaceous ages for some granites in the Nan'ao Island, contradicting with the established trend. To address such controversy, we have carried out geochronological and geochemical studies of several granite plutons in this island. New zircon U-Pb age data show that they were emplaced in the Early Cretaceous from ∼ 141 Ma in the Dajianshan area to 123–121 Ma in the Forest Park and Hulu-Guolaoshan areas, confirming that the southeastward younger trend of granitic magmatism had reached Nan'ao Island. These granites are characterized by high SiO2 (74.2–77.8 wt%) and low Al2 O3 (12.0–13.1 wt%) contents, pronounced negative Ba-Eu-Sr-Ti anomalies, and moderately high temperatures of magmas (TZr  = 655–771 °C; TLREE  = 675–819 °C). The Dajianshan granites have lower εNd (t) (−3.9 to − 3.6), Nb/Ta (6.8–12), and Zr/Hf (16–22) than the Forest Park and Hulu-Guolaoshan granites (−1.5 to + 1.1, 9.4–16, and 20–30). The new data support the interpretation that the parental magmas for the Dajianshan granites were derived from a mixture of juvenile crustal rocks and Proterozoic metamorphic rocks whereas the parental magmas for the Forest Park and Hulu-Guolaoshan granites were sourced from juvenile crustal rocks. We envision that partial melting in the crust was induced by underplating of mantle-derived mafic magma, which in turn was produced by decompression melting of ascending asthenospheric mantle in response to rollback of the subducting Paleo-Pacific plate.